Observaciones sobre el mesolitoral rocoso de la zona de Ushuaia (Tierra del Fuego, Argentina) - Zaixso, H. E.; Boraso de Zaixso, A. L.; López Gappa, J. J. (Ecosur, 2025)
Flora and fauna composition on the mesolittoral of rocky shores at five localities near Ushuaia are studied. Only two horizons are proposed to describe their vertical distribution.